Note on Germination of Spruce Seeds with Gibberellic Acid - Chandra, J. P.; Chauhan, P. S. (Indian Forester, 1976)
Gibberellic acid was used for improving seed germination of spruces Soaking of seeds in 500 ppm solution gave as good results as soaking in 750 and 1000 ppm. Germination percentage of a seed sample which had 30 percent germination one and half years before, was recorded as, 25, 58, 74, 75 and 80 after soaking them in water, 250 ppm., 500 ppm., 750 ppm, and 1000 ppm. Gibberellic acid solution respectively.